(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
For the most people, change is something that is achieved through agreement. Most people can basically say that they all are living in freedom and with some kind of liberty. Then, imagine that suddenly an outsider comes in to the home and starts imposing rules and making changes that all have to obey, or risk severe punishment for disobeying. After a period of time, the family cannot handle it anymore, decides to finally tell the unwanted guest to get out of the house. When he is gone they realize that he has destroyed a lot and try to go back to their original rules but don’t know where to start. The world and family has changed so much that returning to the past way of thinking will not work anymore (Scattergood, 3)